Ecología de una población de Teius oculatus (Sauria: teiidae) de Río Cuarto (Córdoba) : I. Estructura poblacional y crecimiento individual - Acosta, Juan Carlos (1990)
Using the mark-recapture method a population of Teius oculatus was studied during four month (dic. 2/1987-march 22/1988). The poblational density was measured, age groups were defined the anual cycle was described and the individual daily growth was calculated to test differences between age groups and the posible correlations between growth and individual snout vent length. Density was different for each period, the age groups were three: hatching juveniles and adults, with change during the active period, being hatching the last in retiring. Individual growth rate changed for each age group and growth and snout vent length are negatively correlated.